2005
DOI: 10.14411/eje.2005.061
|View full text |Cite
|
Sign up to set email alerts
|

Role of (E)-β-farnesene in systematic aphid prey location by Episyrphus balteatus larvae (Diptera: Syrphidae)

Abstract: Abstract. The foraging behaviour of beneficials such as aphidophagous predators depend largely on volatile compounds emitted by potential preys. Even if polyphagous predatory species are considered, all the potential preys are not systematically localised and accepted. In this work, chemical cues from different aphids and plants, each alone or in association, were studied to elucidate their role in prey location. Using a four-arm olfactometer, attraction of combinations of three aphid (Megoura viciae, Acyrthos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
78
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 15 publications
0
78
1
1
Order By: Relevance
“…Almohamad et al, 2007Almohamad et al, , 2009). Infochemical cues emitted from aphids are also known to increase the foraging efficiency of predatory hoverfly larvae (bargen et al, 1998;Francis et al, 2005). Chandler (1969) reported that aphidophagous hoverfly larvae start moving directly until their first tactile contact with aphids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almohamad et al, 2007Almohamad et al, , 2009). Infochemical cues emitted from aphids are also known to increase the foraging efficiency of predatory hoverfly larvae (bargen et al, 1998;Francis et al, 2005). Chandler (1969) reported that aphidophagous hoverfly larvae start moving directly until their first tactile contact with aphids.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are consistent with the findings of bargen et al (1998) who suggested that the prey location of E. balteatus larvae may be guided by the aphid-born volatiles when searching for prey. There is evidence that E. balteatus larvae respond to olfactory volatile chemicals associated with different aphid species, (Acyrthosiphon pisum, Megoura viciae and Aphis fabae: Francis et al, 2005). theory suggests that the intensified search (random, non directional search) in a small area helps the insect predator to find sufficient food if the prey is distributed in clusters (Murdie, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Broad beans, V. faba, have been largely used in the study of the oviposition behavior of hoverflies, demonstrating its suitability for this aphidophagous predator within pest management strategies (e.g. Vanhaelen et al 2001;Francis et al 2005b;Verheggen et al 2008). Potatoes have also been presented as suitable host plants for hoverfly female oviposition (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the aphid alarm pheromone (E)-β-farnesene (EβF) is secreted by at least 16 aphid species (Francis et al, 2005a) but to which the Brevicoryne brassicae does not show their aposematism. Therefore, it has been suggested that EβF role is to distinguish conspecifics from host plant rather than as an alarm signal by B. brassicae (Francis et al, 2005b). As a huge and diverse group, insects have been estimated to have 4-5 million species (Novotny et al, 2002) and occupy numerous different habitats.…”
Section: Introductionmentioning
confidence: 99%